Numerical study of effect of spoiler configuration on wake vortex alleviation - Ludin@Jamaluddin, Hani; Omar, Ashraf Ali; Asrar, Waqar (American Society of Civil Engineers, 2015)
A numerical investigation was undertaken to evaluate the capabilities of differential spoiler setting (DSS) in modifying the span-wise wing load and reducing hazard of wake vortices imposed on a following aircraft. Numerical simulations were carried out on a scaled, half-model aircraft under high lift configuration (HLC) condition for two outboard loading cases and two inboard loading cases, in addition to the baseline configuration case. The study has covered the near-wake field and the extended near wake field regions. The results are presented in terms of velocity contours, vorticity contours, tangential velocity, circulation and streamlines at several measurement sections downstream, namely at x/b=0.345, x/b=0.444, x/b=0.658, x/b=1.794 and x/b=4.484 measured from the wing-tip trailing edge. Comparison between numerical simulations and experimental results has shown good agreement in terms of lift coefficients for all cases, and fairly acceptable agreement in terms of maximum crossflow velocity, maximum normalized total circulation and maximum induced rolling moment. However, in some cases the agreement is not good. Evaluation of the results has showed promising outcomes for the inboard loading cases compared to the outboard loading cases which agree with the experimental results. The interaction between spoilers' wake and outboard flap tip vortex of the inboard loading cases reduces the tangential velocity magnitude and circulation of the wing tip vortex, delays vortex merging to farther distance downstream, and thus, minimizes the induced rolling moment imposed to the following aircraft. Therefore, DSS can be considered as one of the promising techniques in wake vortex alleviation that can be used commercially in the future. The only limitation of this study is the need of more sophisticated computational resources to benefit from using finer mesh which can minimize the difference between numerical and experimental results. This should therefore enable to extend the study of wake vortices for the very far-wake field or up to a distance where the following aircraft is usually located.